An Asian Monetary Union? - Lau, Evan; Siti Nur Zahara, Hamzah; Choong, Xin-Yi (EbscoHost, 2012)
This study examines the validity of the long run purchasing power parity (PPP) hypothesis using a battery of both univariate and panel unit root tests for 10 Asian countries against Chinese Yuan and Japanese Yen. We found evidence against mean reverting when Yuan is used as the numeraire while stronger evidence of the parity condition with the Yen based rates based on Breuer et al. (2002, SURADF). The initiation of the Asian Monetary Union may be foreseeable with Japan as the leader, it could start off with selected countries.